Consumer perceptions towards healthier meat products. (April 2021) - Teixeira, Alfredo; Rodrigues, Sandra
Highlights: Consumers perceptions towards healthier meat products was reviewed. Consumers are concerned and can be influenced by claims of healthy products. Consumers are willing to pay for sustainable and healthier products. Healthier products can be obtained by replacing animal fat and salts. When producing healthier products consumers must be consulted. Abstract : Consumer perceptions towards healthier meat products are now mainly associated with how meat is produced and processed; the physical and chemical composition; nutritional quality; sensory properties, and social, ethic, or religious aspects. The main purpose of this condensed review was to summarise the most recent studies on the consumer perceptions towards healthier meat products and contribute to a better knowledge and social awareness about the healthiness of meat products by disseminating the available information.